Penerapanlangkah Polya dalam Menyelesaikan Soal Cerita Keliling dan Luas Persegipanjang - Marlina, Leni (Jurnal Elektronik Pendidikan Matematika Tadulako, 2013)
The purpose of this research is to describe the implementation of Polya phase that can improve student learning outcomes in solving word problems about rectangular in VII A SMP Negeri 19 Palu. This type of research is a classroom action research. Plan of this research is based ofÂ Kemmis and Mc. Taggart. Based on the result of the research learning to use Polya phase can increase the studentâs learning outcomes to solving the word problem about rectangular in VII A SMP Negeri 19 Palu, those are: 1) understanding the proble; 2) devising plan, 3) carrying out the plan;and 4) looking back at a complete solution.